PENGARUH BAGI HASIL DAN PENDAPATAN PER KAPITA TERHADAP PENINGKATAN DANA PIHAK KETIGA - Lina Marlina; Jajang Iskandar (Universitas Siliwangi, 2019)
The purpose of this study is to find out how profit sharing and per capita income affectson third party funds both partially and simultaneously. The research was conducted at BankJabar Banten Syariah KCP Singaparna period 2011 - 2013. In this study the authors used thecorrelational method with a quantitative approach. Data are gained through field research,using multiple regression analysis as the test tool. The results of the study show that profitsharing, per capita income and third party funds are fluctuatively increasing as well asdecreasing; Profit Sharing partially has a significant effect on Third Party Funds; Per Capitaincome partially has a significant effect on Third Party Funds; Profit Sharing and Per CapitaIncome simultaneously have a significant effect on Third Party Funds at Bank Jabar BantenSyariah KCP Singaparna in the period 2011 - 2013